PENGARUH PENERAPAN KONSEP DIGITALISASI DI MUSEUM SONOBUDOYO YOGYAKARTA - Friska Ariani Br Sitepu; Annisaa Nurul Atiqah (Kepariwisataan: Jurnal Ilmiah, 2022)
Sonobudoyo Museum Yogyakarta is a state museum that has the second largest number of collectibles in Indonesia. In 2019 the application of digitization was carried out on several museum collection objects. The purpose of implementing digitization at the Sonobudoyo Museum is to provide visitors with the convenience of providing information on collections of objects. This research was conducted to observe the effectiveness of the application of digitalization at the Sonobudoyo Museum in attracting tourist visits. The method used in this research is descriptive qualitative. The description includes internal and external factors in tourism objects. The data found were analyzed using SWOT to describe the results in the historical and cultural tourism object of the Sonobudoyo Museum, Yogyakarta. Based on the results of observations, interviews and documentation, it can be concluded that the effectiveness of the application of digitalization provides satisfaction to tourists with a satisfaction level of 96%. Based on the visit data, there was an increase in visits of more than 50% after the application of the concept of digitization was applied at the Sonobudoyo Museum, Yogyakarta.Keyword: Sonobudoyo Museum, Yogyakarta State Museum, Effectiveness of Digitalization Implementation